Van Opstall, E.M. (2019). Sacred Thresholds. The Door to the Sanctuary in Late Antiquity - Caseau, Beatrice (ARYS. Antigüedad: Religiones y Sociedades, 2020)
VAN OPSTALL, EMILIE M. (ed.) (2018). Sacred Thresholds. The Door to the Sanctuary in Late Antiquity. Religions in the Graeco-Roman World, 185. Leiden and Boston: Brill. 376 pp., 252,00€ [ISBN 978- 9-0043-6859-0] [Book review]